Improvement of traction-traction fatigue properties of A100 steel plate-hole-structure by double shot peening. (September 2022) - Zhi, Yinglin; Zhang, Xiaohua; Liu, Daoxin; Yang, Jing; Liu, Dan; Guan, Yanying; Shi, Jianmeng; Zhao, Weidong; Zhao, Ruiming; Wu, Junnan; Wang, Junbin; Cheng, Shumin
Highlights: The fatigue limit of DSP samples is improved by 59.6% compared to A100 steel BM samples. The fatigue notch sensitivity of A100 steel samples subjected to DSP decreased to 61%. The compressive residual stress of high-intensity DSP specimens is more stable. DSP introduces more severe plastic deformation on the hole surface than that of plate. The stress concentration at the edge of hole is relieved by DSP treatment. Abstract: To reduce the stress concentration and improve fatigue resistance of A100 steel plate-hole-structure, double shot peening (DSP) of the primary shot peening with strong intensity iron shots and the secondary shot peening with weak intensity ceramic shots is carried on material surface and hole and the effect of surface integrity on fatigue properties is investigated. The results show that the surface of hole presents severe surface plastic deformation (SSPD) with increasing DSP intensity. A high intensity compressive residual stress (CRS) distributed in deep layer is generated. Meanwhile, the compressive residual stress is much more stable during the fatigue process, which is beneficial to improve fatigue properties by inhibiting fatigue crack initiation and early propagation. In addition, due to the reduced stress concentration at the edge of hole and higher compressive residual stress, the fatigue resistance of A100 steel plate-hole-structure is remarkably improved. The average fatigue strength of DSP-treated specimens with medium intensity primary shot peening was at least improved by 59.6%, and the fatigue notch sensitivity was reduced by 61%. However, it is also discovered the secondary shot peening cannot repair the rough surface and surface damage caused by excessive primary shot peening, which compromise the improvement of fatigue resistance.